(untitled) (EDUCATION IN THE 21ST CENTURY, 2023)
Democratization, individualization, dialogism and other trends of modern Armenian education require priority orientation to meet the needs of the person himself, treatment to his rights and freedoms, to formаtion of the ability to overcome social risks, take responsibility for their own destiny and the fate of society and the state. Today the status of education in our society is being changed. Education is no longer regarded as a departmental industry serving the interests of other departments and social practices. In the third millennium, the education system of Armenia should undergo drastic changes, which concern not only to the structure of its organization, methodology and technology for constructing educational processes at all levels of this system, but mainly to redefine the goals of education, its strategic guidelines, and the place in public life that allows to adequately respond to the challenges of the 21-st century. At present, the fundamental dependence of the prospects of our civilization on those abilities and qualities of a person that are gained and formed in education, is already quite obvious. Modern pedagogical thought actively addresses the problem of the anthropological content of education. Education at the present stage in the framework of the development of the humanitarian paradigm not only does not reject the anthropological foundation, but actualizes it more and more. The treatment of pedagogy to the anthropological approach allows to have a new look at the understanding of innovative educational practice both in the historical context and in modern reality. The anthropological approach, as an approach aimed at the social aspect as a result of subject-subject relations in the pedagogical process, allows both the scientist and teacher to consciously follow it in their activities, as well as its systematic, relevant modernity of educational goals, tasks and create conditions for the implementation of the pedagogical process. That is, the anthropological approach in modern pedagogy acts as a method and at the same time a tool for forming the integrity of a person, his holistic culture. The anthropological approach is relevant in the humanitarian paradigm of education, in pedagogical science, since humanitarian knowledge is focused on the individual, touches to a person’s spiritual world, to his personal values and meaning of life.